2016
DOI: 10.1177/1474515116637734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yoga in patients with paroxysmal atrial fibrillation – a randomized controlled study

Abstract: Background: Patients with atrial fibrillation often have an impaired quality of life (QoL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 28 publications
(42 reference statements)
2
46
0
4
Order By: Relevance
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from pooled analysis of eight studies2 25–31 showed 52 deaths in 445 (11.7%) exercising participants and 47 deaths in 438 (10.7%) control participants. There was no significant difference in pooled RR between exercise-based CR and control groups (RR 1.08, 95% CI 0.77 to 1.53, p=0.64, I 2 =0%) (figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, another 12-week intervention of mediyoga, a form of yoga adapted from Kundalini yoga specifically for patients with cardiac disease, has been associated with improvements in quality of life as measured by two validated quality of life instruments. Importantly from a mechanistic standpoint, this study showed a significant decrease in heart rate and blood pressure in the yoga group (Wahlstrom et al, 2017).…”
Section: Yogamentioning
confidence: 63%
“…They found a decreased heart rate and blood pressure, and improvements in quality of life. These findings suggest that stress and anxiety may have a significant role in AF . It still needs to be elucidated whether psychological stress plays a role in the pathogenesis of AF in athletes.…”
Section: Discussionmentioning
confidence: 91%